Antimicrobial Susceptibility Pattern of Staphylococcus aureus Strains Isolated from Hospitalized Patients in Tehran, Iran: Staphylococcus aureus susceptibility pattern - Rasoul Soltani,; Hossein Khalili,; Kheirollah Gholami,; Mehrnaz Rasoolinejad,; Alireza Abdollahi, (Iranian Journal of Pharmaceutical Sciences, 2010)
Staphylococcus aureus is a major bacterial pathogen that causes different community- and hospital-acquired infections. Over time, strains of S. aureus have become resistant to different antibiotics including penicillinase-resistant penicillins. Having data on the local antimicrobial susceptibility pattern of this pathogen is necessary for selection of appropriate antibiotics for empirical treatment of infections due to it. To determine the antimicrobial susceptibility pattern of Staphylococcus aureus strains isolated from hospitalized patients in Tehran, Iran, In a prospective cross-sectional study performed at Imam Khomeini Hospital, samples were collected from hospitalized patients and were cultured. All positive cultures which yielded S. aureus underwent antimicrobial susceptibility testing using the Kirby-Bauer disk diffusion method on Mueller-Hinton agar. The results were interpreted after 24 hours of incubation at 37 °C. A total of 160 clinical isolates of S. aureus were collected. Most isolates were obtained from blood (29%). The overall susceptibility of isolated S. aureus strains to antimicrobial agents was 100% for vancomycin, 49.4% for amikacin, 43.8% for gentamicin, 36.8% for co-trimoxazole and tetracycline, 36.3% for cefazolin, 30.6% for cephalexin, 24.4% for oxacillin, 23.8% for erythromycin, and 3.1% for penicillin. Other than vancomycin, none of the tested antibiotics are appropriate for empirical treatment of serious S .aureus infections in our area.